2001
DOI: 10.1021/ma001962t
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and ESR Studies of Ring-Opening Radical Polymerization of 1,1-Bis(ethoxycarbonyl)-2-vinylcyclopropane

Abstract: Ring-opening radical polymerization of 1,1-bis(ethoxycarbonyl)-2-vinylcyclopropane (BEVCP) with dimethyl 2,2′-azobisisobutyrate (MAIB) was investigated kinetically in benzene. The overall activation energy (E a ) 94 ( 4 kJ/mol) was calculated from the polymerization rate (Rp) obtained at 30-60 °C. Rp (40 °C) is given by Rp ) k[MAIB] 0.6(0.1 [BEVCP] 1.0(0.1 , which is similar to that of conventional radical polymerizations involving bimolecular termination. The present polymerization system involves ESRobservab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…[31] More recently, the EPR method has been applied to further studies of the polymerizations of styrene, [37,38] acrylates, [39][40][41] methacrylates, [42][43][44][45][46][47] acryland methacrylamides, [48][49][50][51] a-substituted acrylates, [52,53] itaconate and related monomers, [54][55][56][57][58] as well as nonconjugated monomers. [59][60][61] Determination of k p by the EPR method and PLP-SEC has resulted in good agreement for styrene, [7,37] methyl methacrylate, [8,42] dodecyl methacrylate, [43,62] dimethyl itaconate, [22,63,64] and methyl a-(2-carbomethoxyethyl)…”
Section: à3mentioning
confidence: 99%
“…[31] More recently, the EPR method has been applied to further studies of the polymerizations of styrene, [37,38] acrylates, [39][40][41] methacrylates, [42][43][44][45][46][47] acryland methacrylamides, [48][49][50][51] a-substituted acrylates, [52,53] itaconate and related monomers, [54][55][56][57][58] as well as nonconjugated monomers. [59][60][61] Determination of k p by the EPR method and PLP-SEC has resulted in good agreement for styrene, [7,37] methyl methacrylate, [8,42] dodecyl methacrylate, [43,62] dimethyl itaconate, [22,63,64] and methyl a-(2-carbomethoxyethyl)…”
Section: à3mentioning
confidence: 99%
“…After 20 h, the solution was diluted with chloroform (5 mL) and added to diethyl ether (300 mL). The resulting white precipitates were collected by filtration with suction and dried under vacuum to obtain polymer 2a (101.1 mg, 67%): 1 According to the typical procedure, 1c was polymerized in toluene to obtain polymer 2c (285.6 mg, 53%): 1 H NMR (CDCl 3 ): d 7.46 (2H, brd, J 5 7.6 Hz, NH 3 2), 5.52 (2H, brs, CH@CH), 4.43 (2H, dd, J 5 5.2, 7.6 Hz, NACH 3 2), 3.73 (6H, brs, OCH 3 3 2), 2.55 (4H, brs, CH 2 ACH@CHACH 2 ), 2.20-2.12 (2H, m, CH(CH 3 ) 2 3 2), 0.90 (12H, t, J 5 6.0Hz, CH 3 According to the typical procedure, 1d was polymerized in toluene to obtain polymer 2d (259.3 mg, 45%): 1 H NMR (CDCl 3 ): d 7.32 (2H, br d, J 5 6.8 Hz, NH 3 2), 5.51 (2H, brs, CH@CH), 4.50 (2H, br t, J 5 6.8 Hz, NACH 3 2), 3.72 (6H, br s, OCH 3 3 2), 2.51 (4H, brs, CH 2 ACH@CHACH 2 ), 1.60 (6H, brs, CH 2 CH(CH 3 ) 2 3 2), 0.92 (12H, t, J 5 4.0Hz, CH 3 According to the typical procedure, 1e was polymerized in toluene to obtain polymer 2e (639.3 mg, 71%). 1…”
Section: Radical Rop Of Vinylcyclopropanesmentioning
confidence: 99%
“…Vinylcyclopropane (VCP) derivatives have attracted considerable attention as cyclic monomers undergoing RROP. [1][2][3][4][5][6] Among various VCPs, 1,1-disubstituted ones have been investigated most extensively. Their RROPs give the corresponding polymers bearing CAC double bonds in the main chains, often accompanied by a side reaction giving cyclobutane rings (Scheme 1).…”
mentioning
confidence: 99%
“…Until now radical emulsion copolymerization of ECVCP with vinyl monomers remained a challenge for the researchers and no detail report is available in the area. Meanwhile, it has been observed that unsaturated polymers obtained by emulsion copolymerization of dienes with methacrylates undergo cleavage to form telechelic oligomethacrylates [12,13] and have been found to be suitable as precursors in the synthesis of co-networks that will find applications in cell culture and tissue engineering [14]. Considering this, emulsion copolymerization of ECVCP with acrylate monomers may be interesting as the resulting copolymers are expected to have unsaturated cleavage points.…”
Section: Introductionmentioning
confidence: 99%